Binaural integration: a challenge to overcome for children with hearing loss. Issue 6 (December 2017) - Gordon, Karen A.; Cushing, Sharon L.; Easwar, Vijayalakshmi; Polonenko, Melissa J.; Papsin, Blake C.
Abstract : Purpose of review: Access to bilateral hearing can be provided to children with hearing loss by fitting appropriate hearing devices to each affected ear. It is not clear, however, that bilateral input is properly integrated through hearing devices to promote binaural hearing. In the present review, we examine evidence indicating that abnormal binaural hearing continues to be a challenge for children with hearing loss despite early access to bilateral input. Recent findings: Behavioral responses and electrophysiological data in children, combined with data from developing animal models, reveal that deafness in early life disrupts binaural hearing and that present hearing devices are unable to reverse these changes and/or promote expected development. Possible limitations of hearing devices include mismatches in binaural place, level, and timing of stimulation. Such mismatches could be common in children with hearing loss. One potential solution is to modify present device fitting beyond providing audibility to each ear by implementing binaural fitting targets. Summary: Efforts to better integrate bilateral input could improve spatial hearing in children with hearing loss.